High Sierra [videorecording (DVD)] - Walsh, Raoul, 1887-1980; Lupino, Ida, 1918-1995; Bogart, Humphrey, 1899-1957; Huston, John, 1906-1987; Burnett, W. R. (William Riley), 1899-1982 (Turner Entertainment ; Distributed by Warner Home Video, 2006)
A gangster's hard-boiled persona finds itself at war with his compassionate side, a side that will ultimately be his downfall.